Effect of Volcanic Sand-Biocarbon-Zeolith Filtration on pH, EC, and TDS values of karst groundwater - Budiyanto, Eko; Muzayanah, Muzayanah; Kurniawati, Aida; Purnomo, Nugroho Hari (Geomedia Majalah Ilmiah dan Informasi Kegeografian, 2023)
Filtration is a very important process because naturally karst landscapes do not provide good protection against groundwater. This study aims to determine the effect of filtration with sand, biocarbon, and zeolite materials on the pH, EC and TDS values. The research was conducted using an experimental method using three filtration tubes filled with these three materials. Samples were taken from ten different water sources. The results of the analysis show that the filtration process of a combination of sand, biocarbon, and zeolite materials has the effect of increasing the pH value, and decreasing the EC and TDS values. The filtration process through a combination of volcanic sand, biocarbon and zeolith materials simultaneously gives a more significant change in pH, EC, and TDS values compared to filtration with these materials separately.